Open Learning Space: Reinterpretation of Inclusive Education from a Classical Islamic Perspective in the Digital Era - syafi'i, Imam (PAI RAFAH, 2025)
This study examines the integration of classical Islamic inclusive values with contemporary digital education to address current disparities in access and participation. The research aims to uncover how historical Islamic educational practices particularly those rooted in the use of open learning environments like mosques and halaqah can inform inclusive models in modern digital contexts. Using a historical-thematic qualitative approach, this study analyzes classical Islamic texts alongside modern digital platforms such as MOOCs and Universitas Terbuka. The results reveal significant gaps in implementing inclusive principles within current Islamic digital education, particularly in curriculum design, teacher preparation, and institutional coordination. The study proposes an integrative framework that combines universal design, inclusive pedagogy, and spiritual-social evaluation metrics. These findings highlight the potential of revitalized Islamic educational traditions to transform digital learning into a platform for global equity, empowerment, and justice.